Effect of Feed Restriction on the Behaviour and Welfare of Broiler Chickens - Angela Trocino; Peter White; Francesco Bordignon; Valentina Ferrante; Daniela Bertotto; Marco Birolo; Giulio Pillan; Gerolamo Xiccato (Animals, 2020)
Under intensive rearing conditions, the welfare of broiler chickens may be at risk depending on genotype and sex, due to their different growth rates. The practice of quantitative feed restriction may also impact on welfare. This study aimed to evaluate behaviour and corticosterone content in plasma and faeces at different ages using 896 one-day-old chicks housed in 32 pens, allocated to 8 groups, i.e., 2 genotypes (standard vs. high breast yield) × 2 sex × 2 feeding plans (ad libitum vs. restricted, AL vs. FR). The feeding system affected the percentage of standing (9.84% vs. 11.7% in AL vs. FR; p ≤ 0.001), feeding (7.51% vs. 8.17%; p ≤ 0.01) and sitting/lying (67.0% vs. 64.1%; p ≤ 0.001), and the faeces corticosterone content (12.2 vs. 13.6 ng/g in AL vs. FR; p ≤ 0.10). Sex affected the percentage of pecking other chickens, standing and comfort behaviours. Changes in behaviour were recorded between high and standard breast yield genotypes with faeces corticosterone which tended to be higher in the former (p ≤ 0.10). Significant interactions between the main factors and age were observed. Major changes in behaviour were due to feed restriction, which stimulated activity during restriction.